Simultaneous detection of human norovirus GI, GII and SARS-CoV-2 by a quantitative one-step triplex RT-qPCR - Yi, Hua-Wei; Wang, Xian-Mo; Tan, Xin; Ding, Cai-Zhi; Zhang, Chang-Li; Wu, Jia-Hao; Li, Qi; Xin, Chen-Qi; Fan, Wen (Frontiers in Microbiology, 2024)
Background: There are many similarities in the clinical manifestations of human norovirus and SARS-CoV-2 infections, and nucleic acid detection is the gold standard for diagnosing both diseases. In order to expedite the identification of norovirus and SARS-CoV-2, a quantitative one-step triplex reverse transcription PCR (RT-qPCR) method was designed in this paper.Methods: A one-step triplex RT-qPCR assay was developed for simultaneous detection and differentiation of human norovirus GI (NoV-GI), GII (NoV-GII) and SARS-CoV-2 from fecal specimens.The triplex RT-qPCR assay had high detection reproducibility (CV<1%) and sensitivity. The lower limits of detection (LLOD95) of the triplex RT-qPCR assay for each target site were 128.5-172.8 copies/mL, and LLOD95 of the singleplex RT-qPCR assay were 110.3-142.0 copies/mL. Meanwhile, among the detection of clinical oropharyngeal swabs and fecal specimens, the results of the singleplex and triplex RT-qPCR assay showed high agreement.The triplex RT-qPCR assay for simultaneous detection of NoV-GI, NoV-GII and SARS-CoV-2 from fecal specimens has high clinical application value.